Equity in water, sanitation, hygiene, and waste management services in healthcare facilities in Tanzania - Eugene Benjamin Meshi; Keiko Nakamura; Kaoruko Seino; Sharifullah Alemi (Public Health in Practice, 2022)
Objectives: To determine coverage and the reliability of water, sanitation, hygiene (WASH) and healthcare waste management (HCWM) services in healthcare facilities (HCFs) in Tanzania. Study design: Cross-sectional study design. Methods: Data of 1066 HCFs in Tanzania from the 2014-15 Tanzania Service Provision Assessment (TSPA) survey were analyzed. The availability of WASH and HCWM services was examined across facility locations, types, and managing authorities. Descriptive statistics, and bivariate and multivariate logistic regression analyses were performed. Results: HCFs with improved water sources, with functional improved latrines for patients, and using the incineration method to treat sharps waste before final disposal were 81.2%, 70.6%, and 41.3%, respectively. Among the HCFs with improved water sources and with functional improved latrines for patients, 50.9% and 50.6% respectively experienced water outages. Rural HCFs were less likely to have water sources on-site within 500 m (AOR 0.41; 95%CI 0.24–0.68), and soap, running water or alcohol-based hand rub (AOR 0.54; 95%CI 0.37–0.80). Rural HCFs were 0.25 times less likely to have functioning improved latrines for patients than urban HCFs (p < 0.001). Public HCFs were 0.5 times less likely to have an incineration method for sharps waste treatment than private HCFs (p < 0.001). Conclusion: Access inequity in WASH and HCWM was observed in HCFs in rural areas and those under public management. To attain equity and sustainability, investing in improving WASH and HCWM services for both new and renovations projects, must consider the circumstance status of the marginalized society.